2022
DOI: 10.1136/bmjopen-2021-053686
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological trends in opioid-only and opioid/polysubstance-related death rates among American Indian/Alaska Native populations from 1999 to 2019: a retrospective longitudinal ecological study

Abstract: ObjectivesThe rate of drug overdose deaths in the USA has more than tripled since the turn of the century, and rates are disproportionately high among the American Indian/Alaska Native (AI/AN) population. Little is known about the overall historical trends in AI/AN opioid-only and opioid/polysubstance-related mortality. This study will address this gap.DesignThis is a retrospective longitudinal ecological study.SettingUS death records from 1999 to 2019 using the Centers for Disease Control and Prevention Wide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Much interdisciplinary research is needed to wed clinical neuroscience with culturally safe, community-driven treatment and prevention solutions. This study represents an important early step in a much broader process of engaging Indigenous communities with neuroscience to address persistent and widening gaps in SUD and related-health problems ( Qeadan et al, 2022 ; Wendt et al, 2021 ). In addition, replications of these findings in other populations would advance prior evidence of similar processing between AIs and general populations in SUD research ( Evans-Campbell et al, 2006 ; Robins et al, 1997; White et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Much interdisciplinary research is needed to wed clinical neuroscience with culturally safe, community-driven treatment and prevention solutions. This study represents an important early step in a much broader process of engaging Indigenous communities with neuroscience to address persistent and widening gaps in SUD and related-health problems ( Qeadan et al, 2022 ; Wendt et al, 2021 ). In addition, replications of these findings in other populations would advance prior evidence of similar processing between AIs and general populations in SUD research ( Evans-Campbell et al, 2006 ; Robins et al, 1997; White et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a description of the variables' evolution over time was carried out. We carried out an analysis of the correlation between the annual rates of ORM and the DHD of the prescribed opioid drugs globally, excluding medications of the least potential risk of overdose and lowest treatment tier [27] (codeine and tramadol), and separately, based on the frequency of their use or their growth over recent years from the initial descriptive analysis. The relationship between ORM and ODP was analyzed as follows: (1) total ODP, (2) total ODP excluding codeine, (3) total ODP excluding codeine and tramadol, (4) tramadol, (5) fentanyl, (6) tapentadol, (7) oxycodone (unifying presentations with and without naloxone), and (8) morphine.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, given our predominantly White female sample, future research should examine how these variables operate to predict outcomes for people of Color and men who are bereaved by an opioid-related death. Epidemiologic research suggested similar rates of opioid overdoses in White and Black communities and lower rates in Hispanic communities (Kaiser Family Foundation, 2022), a disproportionate impact of the opioid epidemic on Indigenous American communities (Qeadan et al, 2022), and rising levels of opioid-related mortality among Asian American and Pacific Islander individuals in recent years (Townsend et al, 2022).…”
Section: Discussionmentioning
confidence: 99%